Experimental study on startup characteristics of a R290 room air conditioner under various ambient temperatures. (January 2020) - Wang, Che; Wu, Jianhua; Du, Yanjun; Li, Jinbo; Du, Wenqing
Highlights: Startup characteristics under various outdoor ambient temperatures were studied. Sub-atmospheric suction pressures occurred during some cold startups. Lower discharge temperature of R290 caused the condensation of R290 in compressor. Influences of indoor fan control strategy of tested air conditioner were analysed. Abstract: Propane (R290) has been considered as one of the alternatives for air conditioner system because of its zero ODP, low GWP and favourable thermo-physical properties. In this paper, experiments were conducted to investigate the dynamic characteristics and to evaluate the safety issues during the startups of a R290 room air conditioner under various outdoor ambient temperatures. Results indicate that the sub-atmospheric suction pressures occurred and lasted during the cold startup in heating mode under an extreme lower ambient temperature, which were potential hazards due to the high flammability of R290. Moreover, if air conditioner started with a smaller EEV opening and the compressor reached higher frequency much earlier, minimum suction pressures drastically declined. As soon as air conditioner started, almost all of liquid R290 stored in outdoor heat exchanger was drawn into accumulator in tens of seconds and some R290 accumulated in the cold compressor shell within a few minutes, resulting in the "starved" outdoor heat exchanger and "enriched" compressor. Additionally, the superheated R290 at EEV inlet greatly influenced the refrigerant supply to low pressure side, which retarded the increase of suction pressure.